Utopian Phenomenon of the American Dream as the Core Concept of the American Culture - B., Shakenova V. (Farabi Journal of Social Sciences, 2019)
Abstract. Within the anthropocentric paradigm a number of various branches are evolving in modern linguistics. Cognitive linguistics and cultural linguistics along with the universals and variations within its categorical apparatus, in particular the functioning features of the term ‘concept’, are the ones of the outstanding directions within the cognitive science. In cognitive linguistics, the concept is localized in consciousness, therefore concepts are considered to be complex discrete units of consciousness by means of which the human thinking process is fulfilled. Concepts appear to be the storage units of human knowledge and as the consequence contain information about the world, though some of which are considered to be ‘binding’ not only to the particular objects but also to be represented in psyche as the images, pictures, circuits.